An experimental investigation of age discrimination in the French labour market - Peter A. Riach; Judith Rich (Institute for the Study of Labor (IZA), 2006)
In a field experiment of age discrimination, pairs of men aged twenty-seven and forty-seven, inquired, by email, about employment as waiters in twenty four French towns. The rate of net discrimination found against the older French waiter, corresponds to the highest rates ever recorded anywhere, by written tests, for racial discrimination. Discrimination was higher in Paris than in the rest of France.
urn:nbn:de:101:1-2008050287
Keywords: 330